The Role of Government Expenditure on Regional Economic Resilience During Pandemic Covid-19 - Akhmadi, Muhammad Heru; Sumardjoko, Imam; Sumantri, Joko (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2023)
The GDP growth rate in the second quarter of 2020 YoY decreased by 5.32%. This contraction was triggered by the COVID-19 pandemic which had an impact on economic activities. The policy of restricting the mobility of people and the closure of various business sectors has resulted in social and economic problems. This study examines government fiscal instruments to maintain the sustainability of the public economy. The analysis used in this study is a mixed method. Empirical testing is done by using regression techniques. The research variables include regional economic performance, spending on the prevention of COVID-19, spending on social safety nets, and spending on handling economic impacts. The research is also based on a questionnaire conducted with local governments regarding health performance and economic recovery efforts. The data used is a cross-section of the period at the end of the second quarter of 2020. The test results prove that the budget reallocation used for spending on COVID-19 disease control and social safety net spending affects improving the regional economy during the study period with p-values of 0.021 and 0.000. The government, through the Sub-National Budget, continues to refocus spending for economic recovery.